2015
DOI: 10.3324/haematol.2015.136622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rituximab maintenance therapy for aggressive B-cell lymphoma depends on use of rituximab in induction therapy: a meta-analysis of randomized controlled trials

Abstract: Contrary to the established role of rituximab maintenance therapy for advanced follicular lymphoma with a high tumor burden, 1 it remains controversial as to whether rituximab confers advantageous effects for aggressive lymphoma when used as maintenance therapy. Recently, a cardinal study from an Austrian group reported the results of the randomized NHL13 trial, which demonstrated no significant prolongation in event-free survival (EFS) by adding rituximab maintenance for patients with aggressive lymphoma who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The efficacy of rituximab as maintenance therapy in DLBCL was previously evaluated in 3 meta-analysis of RCTs. [24][25][26] One meta-analysis by Nannya et al 24 The third meta-analysis, published by Zhou et al, 26 included 5 RCTs 2, [16][17][18]27 and concluded that males and previously untreated DLBCL patients benefited most from maintenance treatment in terms of EFS and PFS when rituximab was the maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of rituximab as maintenance therapy in DLBCL was previously evaluated in 3 meta-analysis of RCTs. [24][25][26] One meta-analysis by Nannya et al 24 The third meta-analysis, published by Zhou et al, 26 included 5 RCTs 2, [16][17][18]27 and concluded that males and previously untreated DLBCL patients benefited most from maintenance treatment in terms of EFS and PFS when rituximab was the maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have implemented high-dose strategies that are used in lymphoma treatment. 11 Nevertheless, several studies have indicated that low-dose rituximab is sufficiently potent to be effective in treating refractory MG, 6,12 and a minimum of two cycles are needed to prevent potential relapses. 13 A systematic review recommended that a repeat rituximab infusion should be considered 4 to 6 months after a cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The rituximab dose regimens have not been consistent. Most studies have implemented high‐dose strategies that are used in lymphoma treatment . Nevertheless, several studies have indicated that low‐dose rituximab is sufficiently potent to be effective in treating refractory MG, and a minimum of two cycles are needed to prevent potential relapses .…”
Section: Introductionmentioning
confidence: 99%
“…84 Maintenance therapy showed no benefit in EFS when rituximab was used as part of induction therapy and in patients who had prior ASCT. 84 Another meta-analysis included seven studies of 1470 patients with DLBCL who received maintenance rituximab following chemoimmunotherapy induction and in the salvage setting. 85 Rituximab maintenance statistically improved EFS but not OS.…”
Section: Rituximabmentioning
confidence: 98%